Reconstrucción de los horizontes orgánicos tras el incendio en la garriga del Macizo de Garraf (Barcelona) - Serrasolsas I.; Ferran A.; Vallejo V.R. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Litter evolution is studied in plots of increasing age after fire: from 2 months to 30 years. During the first year, the L horizon decomposed quickly. The process was described by the decreasing of the L/F ratio during this period. From second year, the regeneration of the vegetation and the beginning of litterfall allowed the increase of the L horizon. Around 15 years after the fire, the amount of organic matter in the L horizon got a steady state value of 4.8 Tm/ha. The first year after the fire, the constant of decay, k, was about 1.38, which correspond to the especially favourable conditions for decomposition occurring just after the fire. In steady state conditions, the k was 0.3, either for the fraction of L transferred to H plus the fraction of L mineralised In the garrigue community, and for L+F transferred to H plus their mineralisation in the mixed garrigue and pines community.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)